Política de inclusão de microempresas e empresas de pequeno porte: avaliação das compras públicas na Universidade Federal do Ceará-UFC com base na Lei Complementar nº 123/06 - Gonçalves, Paulo Henrique Leite (2020)
The present study has the general objective of evaluating, in a constructivist perspective, the benefits conferred to Microenterprises (MEs) and Small Companies (EPPs) in the scope of public tenders, conferred by Complementary Law (LC) nº 123/06. This law establishes rules regarding the favored, differentiated and exclusive legal treatment given to these companies, which is based on questions of socioeconomic public policies. Therefore, there is an urgent need for the State to grant fair and equal conditions of competition, applying these rules in bidding processes. And, as specific objectives, describe the applicability of this policy in public procurement carried out by the Federal University of Ceará (UFC) in the years 2017 and 2018. The topic covered goes through the definitions of these economic agents and the constitutionality of the regulatory standard, describing the general benefits in the bidding processes initiated within the UFC, with a special focus on bidding exclusivity for MEs and EPPs, imposed by article 48, item I of LC nº 123/06, as well as their practical repercussion when judging the contest, award and hiring the winning company. Finally, expose the exceptions to the non-applicability of benefits, when the aforementioned law imposes. The study identified the demands, concerns and difficulties of public procurement agents in adapting administrative procedures to the terms of the regulations for applying the policy, as well as the degree of economic success or profitability achieved by the Autarchy / UFC and the quality of the product purchased. It is an evaluative, exploratory and descriptive research, with quantitative and qualitative approaches, for this purpose, the method of constructivist evaluation was used, based on the perspective of the Fourth Generation Evaluation of Guba and Lincoln (1989). Which is characterized by being a responsive evaluation, for its inclusive, explanatory and participatory characteristics, in which negotiations are made between the actors involved (stakeholders) in the phenomenon to be evaluated. The collection of information took place between the months of July to November 2019 and the following were used: a semi-structured questionnaire by the author, in order to better understand the attributes of the policy within the scope of the Autarchy / UFC; unstructured interviews with interest groups (managers), aiming to apprehend the dynamics of the internal services of the Pro-dean of Planning and Administration of the Autarchy / UFC (PROPLAD/ UFC) and finally, a round of talks for the consensual construction of a technical contribution on issues raised in the pleading.